Characterization of tailings from the processing of ornamental rocks: Caracterização de relevos provenientes do beneficiamento de rochas ornamentais. - Sousa, Antonio Augusto; Nogueira, Hilda Camila; Araújo, Gabriela de Castro; Sousa, Felipe Augusto; Andrade, Alisson Rufino (Brazilian Journal of Production Engineering, 2021)
The processing of ornamental rocks promotes the constant generation of abrasive sludge, which, in turn, causes different types of contamination. The possibility of reusing residues generated in industrial processes has economic advantages, therefore, it is necessary to know the physical, chemical and mineral properties of these residues. Thus, the objective of this research was to evaluate the possibilities of application of abrasive mud, generated in industries located in the city of Campina Grande - PB, based on its main characteristics. The methodology consisted of the following analyzes: X-ray fluorescence, X-ray diffraction, scanning electron microscopy, particle size analysis and physical-chemical analysis. Chemical analyzes revealed that the residues have interesting characteristics, mainly for use in civil construction. The mineralogical analysis indicated that the sample has an essential mineral composition for the cosmetic industry, which was confirmed by the detected elements present. The study of the particle size characterized the sample as material of irregular shape and with good micronization, confirming the potential for reuse as a cosmetic, while the morphological analysis showed the presence of iron as a limiting factor for certain applications. Physico-chemical tests confirmed the characteristics common to abrasive sludge. The characterized samples showed, in general, satisfactory properties with regard to its use as an alternative material in different segments.
Keywords: Industrial waste; Characterization; Sustainability; Minerals treatment; Reuse